The Role of Islamic Education Teachers in the Middle of Society in Religious Activities - Puja Dikusuma Mardiana; Muhammad Ikhsan; Abelhadji Analka (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
Islamic Education is a compulsory subject in education in Indonesia on the basis of the Qur'an and Hadith, to achieve its learning objectives, namely faith and character, various instruments are needed, one of which is teaching staff. This study aims to find out what the role of a religious teacher is in religious activities in the community. This study uses a qualitative method with a case study approach. Sources of data were taken from five informants through interviews, all informants are active educators from several educational institutions. The results of the study show that the social role of a teacher in religious activities in the community, namely being an imam or lecturer at tarawih prayers and IED prayers, preachers and priests for Friday prayers, teaching at the Qur'an educational parks, committees for commemorating Islamic holidays, and participate in religious social services. This role is also supported by different motives for each informant. The results of this study can be used as initial data for subsequent researchers to further study the same issue.